ANALISIS PENGARUH RASIO LEVERAGE, RASIO LIKUIDITAS, RASIO PROFITABILITAS, PORSI SAHAM PUBLIK, DAN UMUR PERUSAHAAN TERHADAP KELENGKAPAN PENGUNGKAPAN LAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEJ - Abubakar Arif (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2006)
The aim of this research is to find the influence of leverage ratio, liquidity ratio, profitability ratio, the portion of stocks owned by public and company ages on the financial statement disclosure comprehensiveness. This research used 50 manufacturing companies listed at Jakarta Stock Exchange which selected using purposive sampling method. The tools analysis used in this research are multiple regression and ANOVA test. The independent variables are leverage ratio, liquidity ratio, profitability ratio, portion of stock owned by public investors and company age. The dependent variable of this research is the financial statement disclosure comprehensiveness. The results of this research show that simultaneously leverage ratio, liquidity ratio, profitability ratio, the portion of stocks owned by public investors and company age influence the financial statement disclosure comprehensiveness. While, partially only company age that influence the financial statement disclosure comprehensiveness. This research also shows that there is no autocorrelation, multikolinearitas and heteroskedastisitas.